Peran Guru Kelas Dalam Pembentukan Karakter Peserta Didik Di Kelas III SDN 16 Kota Bengkulu - Zubaidah; Ranti Octavia; Sentia Alisah; Nurul Fadilah; Saidina Ali (Yayasan Darussalam Bengkulu, 2023)
This study aims to describe the role of teachers in the formation of student character in grade III SDN 16 Bengkulu City, and what kind of characters teachers often encounter in SDN 16 Bengkulu City, The subjects of this study were teachers and third grade students of SDN 16 Bengkulu City, totaling 35 students, this study used descriptive qualitative research methods, data collection methods in this study used observation, interview, and documentation methods. The results of this study indicate that teachers play a very important role in the formation of student character, such as implementing exemplary attitudes, honesty, responsibility, and independence. After implementing these attitudes, students become better, disciplined, independent, and responsible.